Analisis Determinan Yang Berpengaruh Terhadap Pendapatan Nelayan: (Studi di Desa Mertasinga Kecamatan Gunung Jati Kabupaten Cirebon) - Wartoyo, Wartoyo; Nabila, Putri (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
The total estimated potential of fish resources in 11 Fisheries Management Areas of the Republic of Indonesia (WPPNRI) is 12.01 million tons per year with JTB 8.6 million tons per year. However, from KKP data, Indonesia is still very far from reaching 8.6 million tons per year. Therefore the purpose of this study is to find out; Fuel Oil, fishing gear, and mileage affect fishermen's income in Mertasinga Village, Cirebon Regency. The research method used in this study is Quantitative Inferential using data collection techniques such as primary data, and secondary data. The data analysis used includes a data quality test, classical assumption test, multiple linear regression test, hypothesis test, and determinant coefficient. The results of this study show that partially the variables of Fuel Oil, fishing gear, and mileage affect fishermen's income. This is indicated by the taccount value > ttable, the BBM variable shows the calculation (4,064) > ttable (1,988), the thitung fishing gear variable (3,746) > ttable (1,988), the calculated mileage variable (9,067) > the ttable (1,988). Simultaneously fuel oil, fishing gear and mileage to fishermen's income in Mertasinga Village, Cirebon Regency. This is indicated by the calculation of > Faccount (62.709) > Ftable (2.71) and sig < a (0.000 < 0.05).